A mobilização para aprender a ensinar matemática e desenvolver o universo cognitivo de pibidianos da UFS: uma análise a partir das relações propostas na TAD - Silva, Narinha Mylena Rocha da (2022)
The current changes in the labor market, resulting from technological advances and speed of information, reflect on the teaching model to be offered in schools, considering that it might not structure an education disconnected from the demands of contemporary society. If we want to align those topics, it is essential to think and rethink the schooling model and, as a result, teacher training. To face this challenge, we count on the help of public policies for teachers, such as the Institutional Teaching Initiation Scholarship Program (Pibid) - created to foster, mainly, the initial formation of teachers, being a potential theme for research. Therefore, our investigation aimed to analyze how Pibid-Mathematics (UFS/Campus São Cristóvão) constituted or modified the cognitive universe of the pibidianos, considering the process of building learning to teach mathematical knowledge objects. The respondents were scholarship holders and volunteers who integrated the Pibid-Mathematics Core Program of the Universidade Federal de Sergipe/Campus São Cristóvão. This study has a qualitative approach, with a descriptive and explanatory character, whose procedures and techniques fit into the participatory research tenor, given the interaction between the researcher and the people investigated. We need to emphasize that due to the pandemic caused by COVID-19, both the program's activities and our investigation took place remotely. Initially, we presented a study about initial teacher education and Pibid, culminating with the mapping of research correlated to ours. For data collection and the constitution of the research corpus, we drew upon triangulation with the following instruments and techniques: logbook, accompanied by media files; questionnaire; document analysis; and interviews. To analyze the data, we initially based our observations on the study of the cognitive dimension, so the term cognitive universe was proposed by the Anthropological Theory of Didactics (TAD), created by Yves Chevallard, in the 1990s. Considering that studies, we started from the notions of object, person, and institution and the relationships they establish among themselves. In discussing the knowledge needed for professional teacher training, we also sought support from Maurice Tardif, besides other authors such as J. Luiz Cavalcante, about two levels of investigation - institutional dimension and personal dimension. In conclusion, we could understand how the investigated institution was structured along with its institutional objects and constructed a potential environment therefore, considering the personal relationships established by the pibidianos, it was possible to notice some modifications in the cognitive universe of those subjects, in the sense of being prepared to teach mathematics. The statements given by the participants revealed that the view at the praxis - characteristic of Pibid-Mathematics and considered as a gap in the course by themselves - was essential for these subjects to begin to recognize themselves as teachers. It happens because the production of different knowledge and direct contact with the profession has proved to be a difference in the construction of the professional identity of these undergraduates.